Social Protection in the Maldives : Options for Reforming Pensions and Safety Nets - World Bank (Washington, DC, 2014)
This report aims to assist the Government of the Maldives in designing and implementing social protection reforms, in particular for pensions and safety nets. The report gives an overview of poverty, risk and vulnerability in Maldives and analyzes the role and effectiveness of pensions and social assistance policies in helping poor households mitigate and cope with risks. Based on the analysis, the study delineates a menu of options for reforming the existing pension and social safety net system. The structure of the study follows the issues outlined above. Chapter 1 sets the stage with an overview of growth, inequality, poverty and vulnerability. Chapter 2 discusses old-age pensions and pension reform options. Chapter 3 covers safety nets (social assistance), while annexes describe the data sources and contain the analytical findings underpinning the recommendations. The executive summary details the main findings and policy options proposed in the report.